Expanding Social Insurance Coverage to Informal Workers - Winkler, Hernan; Ruppert Bulmer, Elizabeth; Mote, Hilma (World Bank, Washington, DC, 2017)
The high incidence of informality in developing countries implies that many workers are not covered against important risks, such as unemployment, illness and old-age poverty. Given that expanding the Bismarckian system to include informal workers presents many challenges, several countries implemented non-contributory social insurance programs to expand coverage. However, these contributed to labor market segmentation and are unlikely to be financially sustainable. This note reviews the economic literature dealing with the expansion of social insurance programs and summarizes the main policy insights. It draws on international evidence on social insurance system design and innovations, and the resulting impact on coverage. It also provides general design principles that can apply to unemployment benefits, health insurance, and pensions.